Validation of rapid Helicobacter pylori Stool Antigen Test in Thai patients with dyspepsia - Sony, Ravin (Biomedical Sciences and Clinical Medicine, 2017)
Importance Helicobacter pylori (Hp) eradication therapy is recommended in H.pylori associated dyspepsia and has been shown to improve dyspeptic symptoms in a subset of patients. The noninvasive H. pylori Stool Antigen Test (HpSAT) for diagnosis of Hp infection provides a method of Hp detection which is simpler, faster, and less expensive than other currently available methods. Objective To evaluate the accuracy of the non-invasive rapid HpSAT for the diagnosis of Hp infection compared with the rapid urease test (RUT) and histological examination in Thai patients with dyspepsia. Methods This prospective study was conducted with patients age 18-55 years at the Outpatient Clinic of Lampang Hospital, Lampang, from January 2016 to October 2016. Patients with alarming dyspepsia symptoms (de fi ned as unexplained weight loss, anorexia, early satiety, vomiting, progressive dysphagia, bleeding, anemia, jaundice, abdominal mass, lymphadenopathy, family history of upper gastrointestinal tract cancer, history of peptic ulcer, previous gastric surgery and malignancy) and those who had received acid-suppressive drugs or antibiotics within 2-4 weeks prior to recruitment were excluded. Stool samples from patients who presented with dyspepsia were collected in the morning of the day they were scheduled for esophagogastroduodenoscopy (EGD). Samples were sent to the laboratory for detection of Hp using the rapid HpSAT. Gastric biopsy samples were also taken from two sites, the antrum and the corpus, for RUT and histological examination. Patients were considered Hp positive if one of the two invasive tests, either RUT or histology, was positive. Results Among the 171 patients enrolled in the study, diagnostic indices of HpSAT were: sensitivity 65.3% (95% CI, 53.4-76.0%), speci fi city 100% (95% CI, 96.2- 100%), positive predictive value 100% (95% CI, 92.7-100%), negative predictive value 78.7% (95% CI, 70.4-85.6%), and accuracy 83.9% (95% CI, 78.5-89.8%). Conclusions A positive HpSAT result is accurate for the diagnosis of Hp infection in patients with dyspepsia with no alarming symptoms. In cases where HpSAT is negative, further investigation should be done to determine the cause of the dyspepsia